Champions of the Movement or Fair‐weather Heroes? Individualization and the (A)politics of Local Food. Issue 2 (4th July 2014) - Busa, Julianne H.; Garder, Rebekah
Abstract We ask to what degree consumers who act out movement practices (eg local food consumption) may do so without regard for larger environmental and social justice implications, and how focus on individual concerns reflects the partial (but increasing) neoliberalization and depoliticization of the alternative food movement. Coupling narratives from five citizen‐consumers with analysis of organizational discourse from a major food movement organization in Massachusetts' Pioneer Valley, we examine the interplay of individual and collective identity to point to places where modified discourse and movement tactics may produce more fruitful outcomes (eg greater community food security). Ultimately, we argue that individualistic interpretations of alternative food are reinforced by organizational campaigns that shape collective identity, casting "buying local" as a heroic act, thereby re‐casting others as anti‐heroes. Counteracting individualization with a new politics of possibility should be prioritized, as citizen‐consumers will inevitably determine future landscapes of food, environmental sustainability and social justice.